Frailty and cardiovascular safety of JAK inhibitors versus TNF inhibitors in rheumatoid arthritis: a real-world comparative study of drug effects and patient profiles - Silvagni, Ettore; Bortoluzzi, Alessandra; Occhino, Giuseppe; Bellelli, Giuseppe; Garaffoni, Carlo; Delvino, Paolo; Leoni, Olivia; Valsecchi, Maria Grazia; Scirè, Carlo Alberto; Rebora, Paola (Frontiers in Pharmacology, 2025)
ObjectiveThe aim of this study was to comparatively assess the risk of cardiovascular events (CVEs) in rheumatoid arthritis (RA) patients treated with Janus kinase inhibitors (JAKis) or tumor necrosis factor inhibitors (TNFis) and to explore the interactions with patient profiles [including age, baseline cardiovascular (CV) risk, and frailty, which is a state of decreased physiological reserve, assessed using a validated frailty index (FI) for healthcare administrative databases (AHDs)].MethodsThis retrospective study was based on AHDs of the Lombardy region, Italy (from 1st January 2020 to 31st December 2023). Cox regression models, both crude and adjusted, were applied to estimate the association between treatments and outcomes [CVEs, major adverse cardiovascular events (MACEs), and thromboembolic events (TEs)]. We tested the interaction between the drug treatment and the regulatory agency prescription rule changes [before or after 06th July 2021, the date of the first European Medicine Association (EMA) pronouncement on tofacitinib safety] or patient profiles.ResultsWe identified 7,541 therapeutic courses in 5,563 patients: 2,343 started as TNFi users, 1,443 as JAKi users, and 1,777 started with other drugs (1,459 days of follow-up). The crude incidence rates (IRs) for new CVEs were 16.6 [95% confidence intervals (95% CI): 12.8–21.2] and 18.6 (95% CI: 14.2–23.9) per 1,000 person-years (PYs) for TNFi and JAKi users, respectively. Exposure to JAKis was not associated with a significantly increased risk of CVEs [adjusted hazard ratio (HR): 0.92; 95% CI: 0.64–1.32], MACEs (adjusted HR: 0.71; 95% CI: 0.37–1.33), or TEs (adjusted HR: 1.53; 95% CI: 0.65–3.65) compared to TNFis. Each 0.1-point increment of the FI significantly increased the HR for new CVEs (HR: 1.80; 95% CI: 1.48–2.19), MACEs (HR: 1.66; 95% CI: 1.10–2.51), and TEs (HR: 1.69; 95% CI: 1.03–2.78). When assessing the interaction between the period of drug delivery and the treatment with JAKis on the risk of new CVEs, no significant interaction was observed (p = 0.838), while the interaction was statistically significant for baseline CV risk (p = 0.007).ConclusionRA patients treated with JAKis in real-world settings have a risk of developing CVEs no higher than those of TNFi users, but potential signals remain for TEs, even if the sample was not sufficiently powered. Patient profiles, particularly the frailty, have a more substantial impact on the risk of CVEs than the specific disease-modifying anti-rheumatic drug (DMARD) choice.